ASSESSMENT OF MEDICAL COLLEGE STUDENTS' SATISFACTION WITH THEIR FUTURE PROFESSION - Perepelitsya, Olesya (Continuing Professional Education: Theory and Practice, 2019)
This article is dedicated to discussion of factors and dynamics of medical college students' satisfaction with their chosen profession in the process of professional education. It was determined that most of the medical college students are not satisfied with their professional choice. The main causes of low satisfaction are: incomplete understanding of core of the future activity; lack of interest in the future activity; students' uncertainty about their own competence; and, as a consequence, – a state of doubtfulness of most of the students' even after admission to the educational institution. Higher percentage of students satisfied with their professional choice with expressed will to work in their profession was found among the students-pharmacists, due to their understanding of the core of the future activity. In the education process of students from the specialty "Pharmacy" the satisfaction with professional choice remains unchanged, as well as their interest in the profession. The reason of decrease of will to work is connected with the students' confidence that work in their chosen field won't promote their self-development and self-realization, won't let them become respected, and won't bring them satisfaction with the results achieved in the field of their profession. The quantity of pharmacists, who see the possibility of their skills’ realization in their profession, increases during professional education. The future nurses, as opposed to the pharmacists, show higher interest in their profession, expect to gain satisfaction from the results of their work, hope for a possibility of self-development and self-realization in their professional activity; this is connected with the search and identification of their place in the profession. The results of the study can be used to continue the search and improvement of ways to support the students' confidence in their own abilities during professional education.